High Prevalence of Human Papillomavirus in Vulvar Cancer Among Vietnamese Women: Implications for Vaccination Strategies - D. N. L. Tran; H. N. Vo; T. T. A. Cung; N. D. Tran; H. N. Cao (Cancer Medicine)
ABSTRACT Background Vulvar cancer (VC) is rare; however, its incidence has steadily increased, likely due to increased human papillomavirus (HPV) infections. HPV infection rates vary significantly with age and ethnicity. Data on the VC incidence in Vietnam are limited. Objectives This study aimed to determine HPV infection rates and high‐risk HPV types (HR‐HPVs) and to model HPV causality in co‐infections using a Proportional Attribution (PropAttr) model in Vietnamese VC patients. Methods We investigated primary VC cases (invasive carcinoma) diagnosed at our hospital during 2020–2021. Tumor samples were tested for HPV using quantitative polymerase chain reaction. Recurrent cases and poor‐quality preserved tumor samples were excluded. HPV infection status, HR‐HPV status, and relevant clinicopathological features were analyzed. To estimate the most likely causative HPV genotype in co‐infected lesions, the PropAttr model was applied, attributing genotypes based on their prevalence in mono‐infections. Model reliability was validated using Spearman's correlation analysis. Results Of the 95 cases, 95% were squamous cell carcinoma, and 40% were clinical stage I. The HPV infection rate was approximately 77% (68.4–85.2), and HPV‐16 was the most common subtype. Patients infected with HPV (mean age: 62.8) were younger than those who were not infected (mean age: 71.4) in univariate (p = 0.004) and multivariate (p < 0.001) analyses. While the vulvar pathohistological type was significantly associated with HPV infection in multivariate analysis (p < 0.001), no significant relationship was observed with other factors in univariate and multivariate analyses. The PropAttr model showed significant correlations between attribution estimates and mono‐infection prevalence (HPV‐16: ρ = 0.806, p < 0.001; HPV‐18: ρ = 0.992, p < 0.001; 12 other HR‐HPVs: ρ = 0.880, p < 0.001). A strong negative correlation between HPV‐16 and 12 other HR‐HPVs (ρ = −0.751, p < 0.001) suggested competitive interactions in genotype assignment. Conclusions The HPV infection rate in Vietnamese VC cases was substantially higher than in other Asian populations, indicating a significant public health burden. Our findings reinforce the importance of expanding national HPV vaccination programs and incorporating advanced attribution models to improve HPV‐related cancer risk assessment.